Praktikalitas E-Modul Kesetimbangan Kimia Berbasis Discovery Learning dilengkapi Virtual Laboratory - Sri Mulyani; Hardeli Hardeli (Universitas Negeri Padang, 2022)
The use of teaching materials that have been developed must have a practical category so that teaching materials can be used in the field. This study aims to determine the practicality of the Discovery Learning-Based Chemical Equilibrium E-Module equipped with a Virtual Laboratory. This research is a continuation of previous research, namely research and development research using the plomp development model. This research stage is in the prototyping stage, precisely in prototype III to the assessment stage. The place of this research is located at SMAN 14 Padang. Analysis of the data obtained using the Aiken'V formula. The one to one evaluation test showed that the e-module was interesting both in terms of cover and content, it was clear in the presentation of the material, the language used was easy to understand, the video display made the material easier to understand. Based on the data analyzed by the aiken V formula, in the small group stage a V value of 87,6% was obtained with high practicality, and in the field test stage a V value of 85,1% was obtained in the high category. This data can be proven by the ability of students to solve problems in module E of 78.86% with a very high category.